Computer decision support changes physician practice but not knowledge regarding autism spectrum disorders - Bauer, N.S.; Carroll, A.E.; Saha, C.; Downs, S.M. (Applied Clinical Informatics, 2015)
Objective: To examine whether adding an autism module promoting adherence to clinical guidelines to an existing computer decision support system (CDSS) changed physician knowledge and self-reported clinical practice.Methods: The CHICA (Child Health Improvement through Computer Automation) system, a CDSS, was enhanced with a module to improve management of autism in 2 of the 4 community pediatric clinics using the system. We examined the knowledge and beliefs of pediatric users using cross-sectional surveys administered at 3 time points (baseline, 12 months and 24 months post-implementation) between November 2010 and January 2013. Surveys measured knowledge, beliefs and self-reported practice patterns related to autism.Results: A total of 45, 39, and 42 pediatricians responded at each time point, respectively, a 95-100% response rate. Respondents’ knowledge of autism and perception of role for diagnosis did not vary between control and intervention groups either at baseline or any of the two post-intervention time points. At baseline, there was no difference between these groups in rates in the routine use of parent-rated screening instruments for autism. However, by 12 and 24 months post-implementation there was a significant difference between intervention and control clinics in terms of the intervention clinics consistently screening eligible patients with a validated autism tool. Physicians at all clinics reported ongoing challenges to community resources for further work-up and treatment related to autism.Conclusions: A CDSS module to improve primary care management of ASD in pediatric practice led to significant improvements in physician-reported use of validated screening tools to screen for ASDs. However it did not lead to corresponding changes in physician knowledge or attitudes.Citation: Bauer NS, Carroll AE, Saha C, Downs SM. Computer decision support changes physician practice but not knowledge regarding autism spectrum disorders. Appl Clin Inform 2015; 6: 454–465http://dx.doi.org/10.4338/ACI-2014-09-RA-0084
Keywords: computer-based decision support; pediatrics; clinical guidelines; autism spectrum disorder; primary care; screening